Pituitary adenylate cyclase-activating polypeptide ameliorates vascular dysfunction induced by hyperglycaemia. (July 2018) - Solymar, Margit; Ivic, Ivan; Balasko, Marta; Fulop, Balazs D; Toth, Gabor; Tamas, Andrea; Reman, Gyongyver; Koller, Akos; Reglodi, Dora
Background: Short-lasting hyperglycaemia occurs frequently in prediabetes and poorly controlled diabetes mellitus leading to vascular damage. Pituitary adenylate cyclase-activating polypeptide (PACAP) has been shown to play a protective role in vascular complications of diabetes; moreover, antioxidant effects of PACAP were also described. Therefore, we hypothesized that PACAP exerts protective effects in short-term hyperglycaemia-induced vascular dysfunctions. Methods: After short-term hyperglycaemia, acetylcholine-induced and sodium nitroprusside–induced vascular relaxation of mouse carotid arteries were tested with a myograph with or without the presence of PACAP or superoxide dismutase. Potential direct antioxidant superoxide-scavenging action of pituitary adenylate cyclase-activating peptide was tested with pyrogallol autoxidation assay; furthermore, the effect of pituitary adenylate cyclase-activating peptide or superoxide dismutase was investigated on hyperglycaemia-associated vascular markers. Results: PACAP administration resulted in reduced endothelial dysfunction after a 1-h hyperglycaemic episode. PACAP was able to restore acetylcholine-induced relaxation of the vessels and improved sodium nitroprusside–induced relaxation. This effect was comparable to the protective effect of superoxide dismutase, but PACAP was unable to directly scavenge superoxide produced by autoxidation of pyrogallol. Endothelial dysfunction was associated with elevated levels of fibroblast growth factor basic, matrix metalloproteinase 9 and nephroblastoma overexpressed gene proteins. Their release was reduced by PACAP administration. Conclusion: These results suggest a strong protective role of PACAP in the vascular complications of diabetes.